2017
DOI: 10.1002/ente.201600572
|View full text |Cite
|
Sign up to set email alerts
|

Platinum Nanoparticles Supported on TiO2 Photonic Crystals as Highly Active Photocatalyst for the Reduction of CO2 in the Presence of Water

Abstract: Photonic crystals can delay the propagation of light and increase its path length through a slow‐light effect, which could have immense potential in improving photocatalytic conversion efficiencies. We employed a colloidal crystal template method to synthesize TiO2 photonic crystals (PC‐TiO2), with platinum nanoparticles (Pt NPs) being deposited on the surface of the PC‐TiO2 support at different loading amounts by the gas bubbling‐assisted membrane reduction (GBMR) method. A series of Pt/PC‐TiO2 photocatalysts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 40 publications
0
17
0
Order By: Relevance
“…Films of nanoporous semiconductor PCs can overcome these limitations due to their robust structure and unique set of physical and chemical properties, which allows rational management of photons at the nanoscale to speed up redox reactions. The advantages of photocatalyst semiconductor PC structures make them desirable for a broad range of applications, including generation of hydrogen energy [21][22][23][24] , purification of air and water [1][2][3][4][5]25 , production of chemicals such as ammonia (NH 3 ) 26 , and carbon dioxide (CO 2 ) reduction for environmental remediation [27][28] . Nanoporous semiconductor PCs enable control of light-matter (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Films of nanoporous semiconductor PCs can overcome these limitations due to their robust structure and unique set of physical and chemical properties, which allows rational management of photons at the nanoscale to speed up redox reactions. The advantages of photocatalyst semiconductor PC structures make them desirable for a broad range of applications, including generation of hydrogen energy [21][22][23][24] , purification of air and water [1][2][3][4][5]25 , production of chemicals such as ammonia (NH 3 ) 26 , and carbon dioxide (CO 2 ) reduction for environmental remediation [27][28] . Nanoporous semiconductor PCs enable control of light-matter (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of the composition and complexity of the aqueous matrix on the performance of photocatalysts is a critical aspect to consider for real-life applications and for the translation of fundamental advances in photocatalysis into practical systems that can address real-world problems. Therefore, the effect of the media composition on the photocatalytic performance of a set of TiO 2 -NAA-DBRs produced with T P = 1200 s was27 assessed studying the degradation of 4-CP in various matrices (i.e. Milli-Q H 2 O, tap H 2 O, Torrens river H 2 O, and 10 g L -1 NaCl aqueous solution).…”
mentioning
confidence: 99%
“…This effect could be explained by the fact that platinum nanoparticles act as electron-trapping centers on the surface of TiO 2 [4546]. After the formation of the very first platinum nanoparticles, photogenerated electrons from the silicon nanostructures are transferred to TiO 2 and in sequence to the already formed platinum.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, plasmonic PCs have been intensively investigated to combine both PBG and LSPR effects together in terms of physical appearances and electronic energies for various applications [104][105][106][107][108][109]. An interesting study has been shown for negative photoresist IO (prepared by SiO 2 opal embedding) deposited with gold, where the dual-colored micropatterns (Figure 3) open the door for possible applications in various fields, including cosmetics, optical filters and coatings [104].…”
Section: Nm-based Pcsmentioning
confidence: 99%